Dielectric relaxations of lead zirconate titanate films up to millimeter‐wave frequencies. Issue 10 (12th June 2022) - Manikandan, Suraj; Aruchamy, Naveen; Allirol, Lucas; Girod, Stéphanie; Glinsek, Sebastjan; Defay, Emmanuel; Granzow, Torsten
Abstract: Modern high‐frequency applications critically depend on the availability of data on the dielectric properties of functional materials in the microwave and millimeter‐wave range. This paper investigates the dielectric response of polycrystalline lead zirconate titanate (PZT) thin films prepared by solution deposition at frequencies between 10 MHz and 70 GHz and temperatures of 305–395 K by measuring the S‐parameters of coplanar waveguides (CPW). The real and imaginary parts of the permittivity of the PZT film are de‐coupled from the electrical properties of both the fused silica substrate and the copper electrodes. Two dielectric relaxations are identified: one around 850 MHz, with room‐temperature permittivity dropping from 1080 to 560, and one around 36 GHz, with permittivity dropping below 100, respectively. The low‐frequency relaxation shows a shift to lower frequencies with increasing temperature; it is explained by the conventional Arlt model of mechanical shear mode resonance across the film thickness. The high‐frequency relaxation, which is practically independent of temperature, is attributed to the response of ferroelectric domain walls.